Submesoscale dynamics accompanying the Kuroshio in the East China Sea - Chen, Juntian; Zhu, Xiao-Hua; Zheng, Hua; Wang, Min (Frontiers in Marine Science, 2023)
Submesoscale processes in the ocean are vital for sustaining energy balance across scales. Taking advantage of the high resolution and wide coverage of numerical simulations, which are currently lacking for field observations, we investigated the basic patterns of submesoscale dynamics and mechanisms of corresponding variabilities along with the Kuroshio in the East China Sea. The large-scale western boundary jet serves as a remarkable submesoscale energy reservoir, promoted by steep topographic features. In the discovered hotspots, that is, the continental slope and lee area of the Tokara Strait, long-lasting submesoscale footprints arose in the form of linear patterns of strongly skewed Rossby numbers with maximum values of O(1). Their origin may be derived from the high topographically induced strain rate, which shows a consistent distribution and high correlation with the Rossby number. Corresponding to the characteristics of such active submesoscale processes, kinetic energy wavenumber spectra were visibly flatter than previous estimations of typical two-dimensional geostrophic turbulence and were not temporally fixed under the combined effects of multiple factors. The annual cycle of stratification induces seasonality by affecting mixed-layer instabilities, which control the kinetic and potential energy conversion rates. The tidal periods may be due to tides generating inertia-gravity waves that partially overlap in submesoscale ranges. Various other intermediate periods of variability were probably related to the eddy-caused Kuroshio path meander, which implied a closely coupled dynamical system across scales. Uncertainties come from the ascertainment of the specific contribution ratios of each part, which will be studied in the future.